2019
DOI: 10.1126/sciadv.aaw7756
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine release and gastrointestinal symptoms after gluten challenge in celiac disease

Abstract: Celiac disease (CeD), caused by immune reactions to cereal gluten, is treated with gluten -elimination diets. Within hours of gluten exposure, either perorally or extraorally by intradermal injection, treated patients experience gastrointestinal symptoms. To test whether gluten exposure leads to systemic cytokine production time -related to symptoms, series of multiplex cytokine measurements were obtained in CeD patients after gluten challenge. Peptide injection elevated at least 15 plasma cytokines, with IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 39 publications
8
139
2
Order By: Relevance
“…IL‐2 levels were always below the lower limit of quantitation (0·5 pg/ml) at all time‐points in the healthy volunteers and also at baseline in the coeliac disease patients, but 23 of the 25 coeliac disease patients had elevated IL‐2 levels 4 h after gluten . Unlike ex‐vivo or in‐vitro assays with gluten‐stimulated fresh blood cells, intestinal tissue, or particularly T cell lines and clones, cytokine assessments in serum are unlikely to be prone to significant laboratory artefact and, at least for IL‐2, IL‐8 and IL‐10, appear to be consistent findings after injection of deamidated gluten peptides and for food challenges with 3 or 6 g of gluten protein, and gluten ingested in a variety of formats, such as bread or as vital gluten added cooked in muesli bars, or uncooked in the format used in the present study . Early elevations of IL‐2, IL‐17A, IL‐22 and IFN‐γ after gluten in patients with coeliac disease implicates rapidly activated T cells as their probable source.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…IL‐2 levels were always below the lower limit of quantitation (0·5 pg/ml) at all time‐points in the healthy volunteers and also at baseline in the coeliac disease patients, but 23 of the 25 coeliac disease patients had elevated IL‐2 levels 4 h after gluten . Unlike ex‐vivo or in‐vitro assays with gluten‐stimulated fresh blood cells, intestinal tissue, or particularly T cell lines and clones, cytokine assessments in serum are unlikely to be prone to significant laboratory artefact and, at least for IL‐2, IL‐8 and IL‐10, appear to be consistent findings after injection of deamidated gluten peptides and for food challenges with 3 or 6 g of gluten protein, and gluten ingested in a variety of formats, such as bread or as vital gluten added cooked in muesli bars, or uncooked in the format used in the present study . Early elevations of IL‐2, IL‐17A, IL‐22 and IFN‐γ after gluten in patients with coeliac disease implicates rapidly activated T cells as their probable source.…”
Section: Discussionmentioning
confidence: 95%
“…Circulating levels of interleukin (IL)‐2 are elevated as early as 2 h after gluten food challenge in patients with coeliac disease on a gluten‐free diet, and are closely linked to the onset of gastrointestinal symptoms . A closely related systemic cytokine release phenomenon also occurs when patients with coeliac disease receive an intradermal injection of short, deamidated gluten peptides corresponding to immunodominant epitopes for gluten‐specific CD4 + T cells . Gluten food challenge also elevates the frequencies of gut‐homing gluten‐specific CD4 + T cells in blood 6 days later that can be detected by using overnight interferon (IFN)‐γ enzyme‐linked immunospot (ELISPOT) assay , human leucocyte antigen (HLA)‐DQ2.5‐peptide tetramers and by measuring chemokine (C‐X‐C motif) ligand (CXCL)10 (IFN‐γ‐induced protein‐10), IL‐2 or IFN‐γ in fresh blood incubated with peptides recognized by gluten‐specific CD4 + T cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Objective markers and methods for distinguishing NCGS from coeliac disease in patients on gluten‐free diets will be essential for both clinical practice and designing investigations. Recent studies have found elevated plasma levels of interleukin‐2 after a single gluten challenge, and that double blind, sham‐controlled gluten challenges can distinguish between people with coeliac disease or NCGS, even after prolonged adherence to a gluten‐free diet …”
mentioning
confidence: 99%
“…The study is also the first to describe the use of measuring serum levels of interleukin‐2 after gluten exposure, or injecting Nexvax2, as a marker of gluten‐mediated immune reactivity. We have recently shown that release of systemic interleukin‐2 reflects the re‐activation of gluten‐reactive T cell . Systemic elevation of interleukin‐2, a cytokine almost exclusively secreted by activated T cells, correlates with severity of digestive symptoms when patients with coeliac disease consume gluten .…”
mentioning
confidence: 99%